Runaway electrons, displacement currents, and discharge development in a quasi-homogeneous electric field; Energy Fluxes and Radiation Effects (EFRE); High Current Electronics Discharges with runaway electrons - Beloplotov D. V. Dmitry Viktorovich (2022, 2022)
Title screen